2013
DOI: 10.4102/jsava.v84i1.67
|View full text |Cite
|
Sign up to set email alerts
|

Clinicophysiological and haemodynamic effects of fentanyl with xylazine, medetomidine and dexmedetomidine in isoflurane-anaesthetised water buffaloes (<i>Bubalus bubalis</i>)

Abstract: The present study was undertaken to investigate the sedative, analgesic and clinical effects of xylazine, medetomidine and dexmedetomidine with fentanyl as pre-anaesthetics in water buffaloes and to compare the dose-sparing effect of xylazine, medetomidine and dexmedetomidine on thiopental for induction and isoflurane for maintenance of anaesthesia in water buffaloes. Six male water buffaloes randomly received intravenous fentanyl (5.0 µg/kg body weight) and xylazine (0.05 mg/kg body weight), fentanyl (5.0 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
21
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 22 publications
8
21
2
Order By: Relevance
“…Xylazine, however, caused mild salivation, drooping of lower lips, and relaxation of the neck in the present camels, findings that had been cited in another study (6). Tongue protrusion occurred in camels after xylazine administration, which is similar to the results of another study in water buffaloes (1). Endotracheal intubation has been cited as being difficult in camels because of the narrow oral space (7).…”
Section: Discussionsupporting
confidence: 84%
“…Xylazine, however, caused mild salivation, drooping of lower lips, and relaxation of the neck in the present camels, findings that had been cited in another study (6). Tongue protrusion occurred in camels after xylazine administration, which is similar to the results of another study in water buffaloes (1). Endotracheal intubation has been cited as being difficult in camels because of the narrow oral space (7).…”
Section: Discussionsupporting
confidence: 84%
“…Cardiopulmonary functions were well preserved in all the animals maintained on either isoflurane or sevoflurane. Singh et al (2013) and Bodh et al (2015) also reported isoflurane to be suitable agent for maintenance of general anaesthesia in buffaloes. Sevoflurane has been used in cattle (Seller et al, 2013) and goats (Setoyama et al, 2003) satisfactorily.…”
Section: Resultsmentioning
confidence: 97%
“…Also, sevoflurane appears to offer a more stable heart rate profile in animals (Ebert et al, 1995). Isoflurane has been used as a safe and effective maintenance agent in water buffalo in experimental (Singh et al, 2013) as well as clinical studies (Bodh et al, 2015) but no information is available on the use of sevoflurane in water buffaloes. So, the present investigation was planned to compare the efficacy and safety of sevoflurane and isoflurane in clinical cases of buffaloes undergoing diaphragmatic herniorrhaphy.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was in accordance with earliest studies in dogs but decrease was remained in normal acceptable range (Maney et. al, 2013 andSingh et al, 2013).…”
Section: Respiratory Rate Depressionmentioning
confidence: 99%